Pengaruh Rasio Likuiditas, Rasio Solvabilitas Dan Rasio Profitabilitas Terhadap Financial Distress Dengan Kepemilikan Manajerial Sebagai Variabel Moderasi (Studi Pada Perusahaan Sub Sektor Makanan & Minuman Di BEI Periode 2020-2022) - Fitriana, Laila; Haris, R Abdul; Rahmansyah, Ahmad Iskandar (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This study aims to examine the effect of liquidity ratio, solvency ratio and profitability ratio on financial distress with managerial ownership as a moderation variable in food & beverage sub-sector companies on the IDX for the 2020-2022 period. The type of research used is quantitative research with a descriptive and associative approach. The population in this study is food & beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. Sample determination is carried out using the purposive sampling method. The source of data in this study comes from secondary data in the form of company financial statements. Data collection techniques use documentation methods. The data analysis techniques used are outer model test and inner model test. The results of this study show that liquidity ratio (CR) and solvency ratio (DAR) have no effect on financial distress, profitability ratio (ROE) has an effect on financial distress, managerial ownership is not able to strengthen the effect of liquidity ratio (CR) on financial distress and managerial ownership is able to strengthen the effect of solvency ratio (DAR) and profitability ratio (ROE) on financial distress.